Radioactivity measurements in eastern Lesvos, Greece - Pappa, Filothei (HNPS Advances in Nuclear Physics, 2023)
The radioactive background of the eastern side of Lesvos Island in Greece, an island rich in natural radioactivity, was studied by means of gamma ray spectroscopy. Dose rates and concentrations of natural radionuclides (232Th series, 226Ra and 40K) and 137Cs were measured in-situ and in the laboratory, respectively. A total of twenty soil samples and ten beach sand samples was collected and processed according to the IAEA protocol. For the in-situ measurement and the dose rate determination a portable NaI scintillation detector was utilized. The activity concentration calculations were held in the laboratory, using a high-purity germanium detector. These activity concentrations were also used to estimate dose rates, so as to compare the obtained results with the in-situ measurements. The maximum detected values of activity concentrations of 232Th series, 226Ra, 40K and 137Cs were found to be 190, 90, 960 and 70 Bq kg-1, respectively. As for the dose rates, both measured and estimated, the maximum values were 230 and 190 nGy h-1, respectively. A significant difference regarding activity concentrations and dose rates was observed between the two matrices (soil, beach sand), with the values of soil samples quite surpassing those of beach sand samples. That can be attributed to the granulometry of each matrix. Furthermore, the study attempts to compare the radioactive background between the eastern and the western side of Lesvos Island, with the larger values being found in the eastern part.